Efektivitas Foot Bath terhadap Penurunan Gejala Neuropati Perifer pada Pasien yang Menjalani Kemoterapi - Dora Hastura; Siti Saidah Nasution; Kiking Ritarwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify the effect of foot bath intervention on reducing symptoms of peripheral neuropathy in patients undergoing chemotherapy. The method used is a quasi-experimental pre-test and post-test with a control group design. Data was collected using a Chemotherapy Induced Peripheral Neuropathy Assessment Tool (CIPNAT) questionnaire with a total sample of 66 patients consisting of 33 patients in the intervention group and 33 patients in the control group selected by consecutive sampling technique. The data obtained were analyzed using paired t-tests and t-tests for independent groups. The results showed a difference between the mean value of peripheral neuropathy symptoms in the intervention group and the control group after treatment with a p-value of 0.0001 (p<0.05). In conclusion, a foot bath effectively reduces peripheral neuropathy symptoms in breast cancer patients undergoing chemotherapy. Keywords: Foot Bath, Chemotherapy, Chemotherapy Induced Peripheral Neuropathy